Pengaruh Pemberian NPK Mutiara dan Hormonik terhadap Pertumbuhan Tanaman Kemangi (Ocimum x citriodorum) - Pramesty, Chella Dwi; Nuriyana, Nuriyana; Wirawan, Purnama (Universitas Khairun, 2025)
The productivity of lemon basil (Ocimum x citriodorum) in Indonesia remains below optimal potential due to inefficient cultivation technology implementation, particularly in nutritional management and growth regulation aspects. Soil fertility degradation and limited application of plant growth regulators constitute primary limiting factors in achieving maximum productivity of this aromatic plant. This research aimed to analyze the effects of NPK Mutiara fertilizer and Hormonik application on lemon basil growth, determine optimal dosage combinations of both production inputs, and examine synergistic interactions influencing morphophysiological plant characteristics. The experiment employed a factorial Completely Randomized Design with two independent factors: NPK Mutiara doses (0, 3, 6, 9 g/plant) and Hormonik concentrations (0, 2, 4, 6 ml/l water), generating 16 treatment combinations with three replications. Observed parameters included plant height, flowering age, economic fresh weight, number of leaf stalks, leaves per stalk, and shoot-root ratio. Results demonstrated that the combination of NPK Mutiara 9 g/plant and Hormonik 6 ml/l water provided optimal growth responses with plant height of 68.83 cm, flowering age of 24.00 days, and leaf count of 572.17 pieces. Synergistic application of NPK Mutiara and Hormonik optimized the genetic potential of lemon basil through enhanced primary metabolism efficiency and endogenous hormonal regulation.